2019
DOI: 10.1088/1361-6595/aae91f
|View full text |Cite
|
Sign up to set email alerts
|

Velocity of initial propagation of positive nanosecond discharge in liquid water: dependence on high voltage amplitude and water conductivity

Abstract: This study deals with the effect of water conductivity and high voltage pulse amplitude on the initial velocity of nanosecond discharge in liquid water. As variable parameters, we used water solutions with three different conductivities (2 μS cm −1 , 100 μS cm −1 , 500 μS cm −1 ), and positive high voltage pulses with four different amplitudes (80 kV, 91 kV, 100 kV, 113 kV). The discharge reactor consists of metallic electrodes in a point-to-plane geometry, both immersed in liquid water. The discharge was gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
(34 reference statements)
4
18
1
Order By: Relevance
“…The time-resolved microscopic images of the luminous filament evolving during the primary HV pulse provide fundamental signatures reflecting the discharge mechanism, i.e., the expansion velocity of the luminous fronts, radial dimensions, and the branching dynamics of the luminous filaments. These parameters were recently investigated in [7,8] by employing single-channel ICCD microscopy. Basic outcomes related to the expansion velocity of the luminous front obtained by using 'one ICCD image per one discharge pulse' approach revealed an initial expansion characterised by a constant velocity of~2 × 10 5 m/s (i.e., 200 µm/ns).…”
Section: Case Study A: Luminous Phase Evolving During Primary Hv Pulse Registered With Equal Mcp Gate Widthsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time-resolved microscopic images of the luminous filament evolving during the primary HV pulse provide fundamental signatures reflecting the discharge mechanism, i.e., the expansion velocity of the luminous fronts, radial dimensions, and the branching dynamics of the luminous filaments. These parameters were recently investigated in [7,8] by employing single-channel ICCD microscopy. Basic outcomes related to the expansion velocity of the luminous front obtained by using 'one ICCD image per one discharge pulse' approach revealed an initial expansion characterised by a constant velocity of~2 × 10 5 m/s (i.e., 200 µm/ns).…”
Section: Case Study A: Luminous Phase Evolving During Primary Hv Pulse Registered With Equal Mcp Gate Widthsmentioning
confidence: 99%
“…The initiation and formation of micro-discharges in liquid water driven by nanosecond high-voltage (HV) pulses are conditioned by the ultrafast (fs/ps) response of the structure of the H-bonded matrix to very high (~GV/m) non-uniform transient electric fields. The physical processes behind very likely include the collective re-orientation of individual molecular dipoles and the subsequent disruption of the cohesion due to the ponderomotive electrostrictive forces followed by the formation of nanovoids and the multiplication of charged species [1][2][3][4][5][6][7][8][9][10]. Experiments performed using extremely short pulses (~100 ps) have shown that discharges in liquid water can be formed in the absence of formation of gas bubbles and with minimal thermal effects [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first rough categorization of high-voltage-induced bubbles can be by either coronalike or arc discharge. A very fast (sub-ns) HVD (highvoltage discharge) can in fact lead to corona-like discharge (considered a partial discharge (Bruggeman et al 2016)) without the formation of a bubble (Pongrác et al 2019), as the bubble growth is usually in the µs range and the dissipation energy in liquids is relatively quick. The pre-breakdown phase change is believed to originate from nanosized voids created by electrostriction effect of the local high electric fields needed to create and sustain an electronic avalanche in liquids.…”
Section: High-voltage Dischargementioning
confidence: 99%
“…Transient bubbles are important for studying, bubble-bubble, bubble-interface and bubble-solid interactions, relevant for disinfection studies of microbiological (Lajoinie et al 2016) and biological tissue interactions (Vogel and Venugopalan 2003), enhanced mixing at small scales (Hellman et al 2007), medical applications (Mohammadzadeh et al 2016), cavitation emulsification (Orthaber et al 2020), erosion (Dular et al 2019), cleaning (Song et al 2004) and thermal effects (Dular and Coutier-Delgosha 2013). Outside the cavitation field, they are interesting for plasma in liquids (Horikoshi and Serpone 2017), acoustic emitters (Buogo et al 2009), high-voltage breakdown of liquids (Pongrác et al 2019) and pulsed laser ablation in liquids (Reich et al 2017) studies.…”
Section: Introductionmentioning
confidence: 99%